Socio-Economic Well-Being Of Household In Pulau Ketam: A Case Study On Sungai Lima Village - Goh, Chen Hong (Universiti Malaysia Sarawak (UNIMAS), 2012)
The purpose of this study is to examine the inequality in development between two villages, Pulau Ketam village and Sungai Lima village, which share a geographical location, PuIau Ketam, Klang, Selangor Darul Ehsan. The inequality in development also contribute to the socio-economic well-being of the people on the island especially Sungai Lima village. The residents in the village faces lack of infrastructure and far underdeveloped comparing to Pulau Ketam village, which is regard as a tourist attraction in Klang. This study is to examine the socio-economic well-being of the people in Sungai Lima village. A total of 50 respondents had been selected for the study. The findings of this study show that people in Sungai Lima village are unsatisfied with the infrastructure provided. Future study should emphasize getting more samples for the purpose of generating a more valid and reliable conclusion.